(untitled) (Damascus University Journal for engineering sciences, 2021)
One of the electro-spinning methods (spinning by extrusion) was used to manufacture a membrane of fibers (in micro and Nano fineness) to create a new core for a medical wound dressing. By using an aqueous solution of polyvinyl alcohol and silver nitrate, to spin them into non-woven fabric networks, and treated by heat. It was found that the heat treatment reduced the cationic silver ions in the spun mesh of polyvinyl alcohol and silver into silver nanoparticles. This research was focused on characteristics of microbial growth studying on the Nano films produced, and verifying the ability of electrostatic spinning of this solution (PVA/AgNO3) according to the principle ratios that have been established (concentration PVA (10 wt%) and AgNO3 (2 wt%)) In this research, We have designed a mechanism to spin nanofibers and produce a network consisting of an extruder equipped with an injector with a fine needle (spinning needle) connected to a high voltage of about 20 - 30 kilovolts, an electron microscope, an microbes incubator. Then, it was done by observation the area of ​​the microbial growth inhibition zone of the membranes producing two types of Gram-positive (Staphylococcus aureus) and Gram-negative (Escherichia coli) microbes, the results were compared with the results of other researchers. At the end result, it is concluded that the electrically spun PVA/AgNO3 membrane is a good material for wound dressing as it has structural stability in humid environment as well as high antimicrobial capacity and continuous effectiveness